THE ROLE OF TRUST AS A MEDIATION BETWEEN THE EFFECT OF PERCEIVED USEFULNESS AND PERCEIVED EASE OF USE TO INTEREST TO BUY E-BOOK - Yudiarti, Rr. Fradiani Eka; Puspaningrum, Astrid (Jurnal Aplikasi Manajemen, 2018)
The purpose of this study is to know and explain whether the benefits and ease of using e-books affect the interest in buying e-books. This research is intended to explain and analyze whether the trust mediated the effect of perceived usefulness and perceived ease of use on the intention to buy e-books. This study examines the interest of buying ebooks. By adopting the TAM model, this study proposed trust as a mediator of perceived usefulness and perceived ease of use influence on intention to buy an e-book. The hypotheses were tested statistically using the SEM-PLS model. The results of this study indicate that perceived usefulness has no significant effect on the intention to buy an e-book, Perceived ease of use has a significant effect to the intention to buy e-books, and trusts have been significantly mediated the effect of perceived usefulness and perceived ease of use on the intention to buy an e-book.